Hydrolytic charge‐reversal of PEGylated polyplexes enhances intracellular un‐packaging and activity of siRNA. Issue 4 (11th January 2016) - Werfel, Thomas A.; Swain, Corban; Nelson, Christopher E.; Kilchrist, Kameron V.; Evans, Brian C.; Miteva, Martina; Duvall, Craig L.
Abstract: Hydrolytically degrading nano‐polyplexes (HDG‐NPs) that reverse charge through conversion of tertiary amines to carboxylic acids were investigated to improve intracellular un‐packaging of siRNA and target gene silencing compared to a non‐degradable analog (non‐HDG‐NPs). Both NP types comprised reversible addition‐fragmentation chain‐transfer (RAFT) synthesized diblock copolymers of a poly(ethylene glycol) (PEG) corona‐forming block and a cationic block for nucleic acid packaging that incorporated butyl methacrylate (BMA) and either dimethylaminoethyl methacrylate (DMAEMA, non‐HDG‐NPs) or dimethylaminoethyl acrylate (DMAEA, HDG‐NPs). HDG‐NPs decreased significantly in size and released significantly more siRNA (∼40%) than non‐HDG‐NPs after 24 h in aqueous solution. While both HDG‐NPs and non‐HDG‐NPs had comparable uptake and cytotoxicity up to 150 n M siRNA doses, HDG‐NPs achieved significantly higher target gene silencing of the model gene luciferase in vitro . High resolution FRET confocal microscopy was used to monitor the intracellular un‐packaging of siRNA. Non‐HDG‐NPs had significantly higher FRET efficiency than HDG‐NPs, indicating that siRNA delivered from HDG‐NPs was more fully un‐packaged and therefore had improved intracellular bioavailability. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 917–927, 2016.